Public funding of uterus transplantation: Deepening the socio-moral critique - Lotz, Mianna (Bioethics, 2021)
Human uterus transplantation (UTx)—the most radical and experimental of all current forms of assisted reproduction—gives rise to a range of complex ethical questions, including those related to individual safety, risk, and informed consent. I have argued elsewhere that the wider social impacts and implications of UTx provision must form part of a comprehensive ethical analysis. My socio-moral critique of UTx provision has been responded to with a number of defences of possible public funding of UTx. In this paper I examine a select number of those defences. These include: that UTx provision would address harms and needs that already exist and as such have priority; that UTx provision is fully compatible with the needed reform of the procreative context in which it would be offered; that UTx provision would not necessarily involve legitimation or endorsement of what are widely agreed to be problematic pronatalist or geneticist norms; and that UTx provision is required as a matter of justice and consistency with other practices. Importantly, defenders are not proposing a ceteris paribus justification of UTx provision; nor do my responses to their arguments represent a comprehensive opposition to UTx. Rather, my more limited purpose here is to show that whatever other defences may be given of publicly funded UTx provision, those considered here do not ultimately succeed and therefore do not allay the concerns underpinning the original socio-moral critique.